Effect of potassium metabisulphite and clove oil dipping on some quality properties of pomegranate fruits cv. Salakhani during cold storage - Kasnazany, Sidiq Aziz Sidiq (Sulaimani Journal for Pure and Applied Sciences, 2018)
The experiment was performed using potassium metabisulphite (KMS) at (0, 2 and 4) % and clove oil (CLV) at (0, 1 and 2) % into which the fruits have been dipped for 2 min to study their effect on some quality properties of pomegranate fruits cv. Salakhani under cold storage conditions (5 ±1°C and 80-90 % RH) for 4 months, according to the factorial trial based on completely randomized design with three replicates. The obtained results showed that decay% of treated fruits was significantly decreased by 4% KMS when comparing with the control, as the concentration of both 2% and 4% KMS decreased the juice% compared to the control. In this respect, KMS treatments at all used rates had no effect on weight loss%, peel thickness (mm), peel%, arils% and TA% compared to the control. On the other hand, 4% KMS gave the maximum values of TSS, total sugars and anthocyanins contents. Whereas, statistically no significant differences were observed with clove oil treatments in all measured parameters except 2% CLV which was found effective in anthocyanins content against 1% and control. Application of 4% KMS+2% CLV showed the highest values of TSS, total sugars and anthocyanins contents, however, the lowest values of decay% and ascorbic acid in the same treatments were observed.
Keywords: pomegranate fruits; potassium metabisulfite; clove oil; postharvest fruit quality